2008
DOI: 10.1001/jama.2007.56-b
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention and Metformin for Treatment of Antipsychotic-Induced Weight Gain

Abstract: Lifestyle intervention and metformin alone and in combination demonstrated efficacy for antipsychotic-induced weight gain. Lifestyle intervention plus metformin showed the best effect on weight loss. Metformin alone was more effective in weight loss and improving insulin sensitivity than lifestyle intervention alone. Trial Registration clinicaltrials.gov Identifier: NCT00451399.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
311
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(327 citation statements)
references
References 36 publications
11
311
1
3
Order By: Relevance
“…Lifestyle changes are considered the first line of treatment to decrease cardiovascular risks in people with metabolic syndrome, 30 being more effective than pharmacological interventions. 3,8,15,20,[31][32][33][34][35][36][37][38][39][40] Forensic psychiatrists try to treat obesity on a case-by-case basis by imposing limits on junk food, 41 but systematic control over diet and behavioural contingencies is quite feasible in psychiatric hospitals. 33 A simple measure already taken in the study hospital is to reduce the regular diet to no more than 2400 kcal/day, and therapy for forensic inpatients with metabolic syndrome that supports dietary and activity changes is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle changes are considered the first line of treatment to decrease cardiovascular risks in people with metabolic syndrome, 30 being more effective than pharmacological interventions. 3,8,15,20,[31][32][33][34][35][36][37][38][39][40] Forensic psychiatrists try to treat obesity on a case-by-case basis by imposing limits on junk food, 41 but systematic control over diet and behavioural contingencies is quite feasible in psychiatric hospitals. 33 A simple measure already taken in the study hospital is to reduce the regular diet to no more than 2400 kcal/day, and therapy for forensic inpatients with metabolic syndrome that supports dietary and activity changes is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Klein and colleagues, in their randomized, double-blind, placebo-controlled trial of metformin in children and adolescents taking atypical antipsychotics, found arrested weight gain, as well as improved insulin resistance (Klein et al 2006). Whereas Baptista and associates found that metformin did not prevent olanzapineinduced weight gain in a group of adult patients with schizophrenia (Baptista et al 2006), Wu and colleagues published two studies indicating that metformin, administered to a group of adult patients with schizophrenia on antipsychotics, including olanzapine, was effective in attenuating weight gain and improving insulin sensitivity (Wu et al 2008a;Wu et al 2008b). …”
Section: Introductionmentioning
confidence: 99%
“…One way to explore this might be a randomized controlled trial of risperidone alone versus risperidone plus diet and exercise or versus risperidone plus metformin to prevent weight gain. Metformin, an antidiabetic drug, has been reported to be safe and effective to combat weight gain of antipsychotics in adults (Wu et al 2008) and children (Klein et al 2006). If the treatment including weight gain prevention produced better symptom outcomes than risperidone alone, then weight gain would be a negative mediator of some clinical value, and the behavioral effect would add to the physical health value of preventing excessive weight gain.…”
mentioning
confidence: 99%